Abnormal Glucose Metabolism and Insulin Resistance Are Induced via the IRE1α/XBP-1 Pathway in Subclinical Hypothyroidism - Xu, Chao; Zhou, Lingyan; Wu, Kunpeng; Li, Yujie; Xu, Jin; Jiang, Dongqing; Gao, Ling (Frontiers in Endocrinology, 2019)
Subclinical hypothyroidism (SCH) and diabetes mellitus are closely related and often occur together in individuals. However, the underlying mechanism of this association is still uncertain. In this study we re-analyzed the data of a mature database (NHANES, 1999 ~ 2002) and found that both fasting plasma glucose levels and the proportion of hyperglycemic subjects among SCH patients were higher than that found in euthyroid controls. SCH was also associated with a 2.29-fold increased risk for diabetes. Subsequently, we established an SCH mouse model and subjected it to an oral glucose tolerance test (OGTT) and an insulin tolerance test (ITT). SCH mice exhibited impaired glucose and insulin tolerance. Increased HOMA-IR and decreased ISI indexes, indicating insulin resistance (IR), were also observed in the SCH state. Hepatic ERp29 and Bip, as well as IRE1α and XBP-1s, were induced significantly in SCH mice, suggesting the induction of endoplasmic reticulum (ER) stress, particularly involving the IRE1α/XBP-1s pathway. Interestingly, when we relieved ER stress using 4-phenyl butyric acid, abnormal glucose metabolism, and IR status in SCH mice were improved. Our findings suggest that ER stress, predominantly involving the IRE1α/XBP-1s pathway, may play a pivotal role in abnormal glucose metabolism and IR in SCH that may help develop potential strategies for the prevention and treatment of diabetes.